Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.269
|View full text |Cite
|
Sign up to set email alerts
|

Gender (In)Consistent Communication via Social Media and Hireability: An Exploratory Study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 49 publications
2
8
1
Order By: Relevance
“…Women were more oriented towards the communication behaviors and this was also supported by the findings of the current study. Likewise, the findings of Brouer et al (2017) was in support with the findings of the present study that the interaction of female Facebook users on Facebook is perceived as most hirable and attractive whereas male Facebook users were found to be less hirable and attractive. This shows the influence and communication bridging of female users on Facebook with their colleagues, family, and friends.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Women were more oriented towards the communication behaviors and this was also supported by the findings of the current study. Likewise, the findings of Brouer et al (2017) was in support with the findings of the present study that the interaction of female Facebook users on Facebook is perceived as most hirable and attractive whereas male Facebook users were found to be less hirable and attractive. This shows the influence and communication bridging of female users on Facebook with their colleagues, family, and friends.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, this study has ascertained that female enrolled as Facebook users tend to communicate and interact with their colleagues, family, and friends. However, the specific finding was in contrast with previous studies, which found that there was a significant difference in the perspectives of Arabic users (Brouer et al, 2017;Thompson & Lougheed, 2012). Lastly, the findings of this study will help to further the understanding of patterns based on communication behaviors, language features, and social behaviors on gender differences of Facebook users as a population group.…”
Section: Theoretical Implicationscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, a study by Slovensky and Ross (2012) found that 70% of hiring managers have rejected a job candidate based on the information that they had found about them on social media. The influence of a job candidate's social media presence on a prospective employer has also been confirmed in studies by Brouer et al (2017) and Baert (2018). The Baert (2018) study found that a job candidate's Facebook profile photo can increase job interview invitations by 38% and can positively impact hiring chances when the candidate is highly educated, and the recruiters are female.…”
Section: Social Media's Influence On Employers' Recruitment Decisionsmentioning
confidence: 74%
“…To date, the majority of literature exploring social media use by employers, employees and job seekers has fallen within two broad categories: social media's influence on employers' recruitment decisions and the professional social media behaviours of job seekers and employees (Melanthiou, Pavlou & Constantinou, 2015;Slovensky & Ross, 2012;Brouer, Stefanone, Badawy, & Egnoto, 2017;Baert, 2018;De Gagne et al, 2018;Pereira et al, 2015;Langenfeld, et al, 2014). The literature has explored how social media is being used by employers and recruiters as a tool to source suitable job candidates for specific roles and to assess the suitability of candidates based on an audit of their digital footprints or social media profiles (Nikolaou, 2014;Aggerholm & Andersen, 2018;Saros-Rogobete & Sav, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%